The Effect of Visual Merchandising on Impulsive Buying with Impulsive Buying Tendency As Moderating Variable - Novia, Jessica (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
This research aims to classify the female consumer demographic segments linked by impulsive buying, to determine the effect of visual merchandising on impulsive buying, and to determine the effect of visual merchandising on impulsive buying with impulsive buying tendency as moderating variable on customers of Gaudi in Taman Anggrek Mall. This research is quantitative research with a total sample of 100 people. Data were obtained by distributing questionnaires to the respondents by cross sectional. Research used Cluster Analysis and Moderated Regression Analysis. Data processing was performed using SPSS software for Windows version 20. Research found that customers of Gaudi were divided into three groups: the way of the world, sufficient money, and promotions. Then, research found that visual merchandising affected impulsive buying. In addition, there visual merchandising had also an effect on impulsive buying with impulsive buying tendency as moderating variable. As a conclusion, moderating variable strengthens the effect of visual merchandising on impulse buying.